Involvement of local community desa pakraman in school counseling supervision - Indriaswuri, Retno; Suranata, Kadek (Jurnal Pendidikan dan Pengajaran, 2018)
Supervision is one of the key program to improve guidance and counseling at school. To increase the quality of supervision, community should be involved. Therefore, this research aimed at analyzing traditional community in Bali who might take part in the program. This literature review surveyed and analyzed articles and books related to supervision in guidance and counseling, community involvement in guidance and counseling, and traditional community in Bali. Result shows that desa pakraman, a traditional community in Bali, is potential to take part in the supervision because the community respect and obedient to every regulation issued by paruman, the highest hierarchy meeting in desa pakraman.